2024
DOI: 10.3389/fpsyg.2024.1332124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and resilience on the dose–response function between the number of adversity factors and subjective well-being

Shulan Hsieh,
Yun-Hsuan Chang,
Zai-Fu Yao
et al.

Abstract: BackgroundEncountering challenges and stress heightens the vulnerability to mental disorders and diminishes well-being. This study explores the impact of psychological resilience in the context of adverse events, considering age-related variations in its influence on well-being.MethodsA total of 442 participants (male vs. female =48% vs. 52%) with a mean age of 41.79 ± 16.99 years were collected and completed the following questionnaires Brief Betrayal Trauma Survey (BBTS), Brief Resilience Scale (BRS), Peace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…This implies that training and education in general increase an individual's ability to be resilient in the face of adversity. A study by Hsieh et al (2024) revealed that resilience is vital for mitigating the effects of adversities on overall well-being. In a study referring to recent events where organizations have had to implement forced change, resilience is a way of surviving.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that training and education in general increase an individual's ability to be resilient in the face of adversity. A study by Hsieh et al (2024) revealed that resilience is vital for mitigating the effects of adversities on overall well-being. In a study referring to recent events where organizations have had to implement forced change, resilience is a way of surviving.…”
Section: Introductionmentioning
confidence: 99%